PCT degradation with electrooxidation (EOx) and ultrasound (US) hybrid process using different type electrodes: BDD, Ti/PbO2 and Ti/Pt - Karaoglu, Aybike Gul; Ozturk, Dilara; Akyol, Abdurrahman; Kara, Serdar (Elsevier, 2023)
In this work, paracetamol (PCT) containing synthetic wastewater was investigated by electrooxidation (EOx) and ultrasound (US) hybrid process. Firstly, anode type (BDD, Ti/PbO2, and Ti/Pt) and process types including ultrasound (US), electro-oxidation (EOx) and hybrid process (EOx-US) were investigated for the degradation of paracetamol (PCT). The PCT degradation efficiency for US, EOx and EOx-US using BDD anode were obtained as < 1%, 70.5 % and 92.4 %, respectively. US-EOx process was found the most effective process in PCT and TOC degradation by using BDD electrodes because of the synergistic effect between sonolysis and electrocatalysis. Then, the effects of operation parameters such as US frequency (100-600 kHz) and US power (25-100 W), conductivity (3500-5500 mu S cm- 1), current density (50-500 A m-2), initial PCT concentration (20-500 ppm) and pH (2-8) on the PCT degradation with time dependency by EOx-US hybrid process were investigated. The optimum conditions were found as 200 kHz, 75 W, pH 2, 4500 mu S cm-1, 100 A m- 2, and 100 ppm when the PCT and TOC degradation efficiencies and the operating circumstances were considered. Additionally, the toxicity of the treated wastewater was examined, and it was discovered that the byproducts' formation caused the inhibition ratio to rise, making the solution more toxic than the initial solution. Frequency effect has not been studied much in hybrid processes in the literature, and it makes this study in this sense valuable.
Keywords: Boron doped diamond; Electrooxidation; Hybrid process; Mixed metal oxides; Paracetamol; Ultrasound